Characterization of the complete chloroplast genome of Prunus clarofolia C.K. Schneid (Rosaceae). Issue 10 (3rd October 2021) - Song, Yan-Feng; Ye, Qi; Yi, Xian-Gui; Wang, Xian-Rong; Li, Meng
Abstract: Prunus clarofolia is an endemic species that widely distributed in subtropical regions of China. Here we present its complete plastome. The plastome of P. clarofolia is successfully assembled from raw reads sequenced by Illumina Hiseq 2500 platform system. The complete chloroplast of this species is 158, 053 bp in length with 36.7% overall GC content, including a pair of invert repeat regions (IR) (26, 393bp) that is divided by a large single copy region (LSC) (86, 088bp) and a small single copy region (SSC) (19, 179bp). The plastid genome contained a total of 130 genes, including 85 coding genes, 8 rRNA genes, and 37 tRNA genes. Each of rps 16, atp F, rpo C1, clp P, pet B, pet D, rpl 16, rpl 2, ndh B, and ndh A contains one intron, rps 12 and ycf 3 contains two introns. Phylogenetic analysis indicates that P. clarofolia has a closer relationship with P. avium .